A role for microRNA-21 in the regulation of gastrointestinal health and disease - Johnston, Daniel (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2017)
The gastrointestinal (GI) tract is a crucial site of innate and adaptive immune regulation, balancing tolerance of beneficial commensal microorganisms and reaction to invading pathgens. Pattern recognition receptors (PRRs), including Toll-like receptors (TLRs), are vital sensors in the orchestration of these immune responses to maintain intestinal homeostasis. Furthermore, these responses must be tightly regulated to ensure an appropriate level of response. There are multiple classes of regulators including non-coding RNA microRNAs which regulate mRNA expression. In this project, we sought to explore the role of microRNA-21 (miR-21) in intestinal health and disease. miR-21 is considered to be an anti-inflammatory regulator in various contexts in immunity, with the negative regulation of TLR4 signalling being of particular interest. However, it has also been shown to be deleterious in cancer and its expression is elevated in patients with several inflammatory disease including inflammatory bowel disease (IBD). Using specifically generated transgenic mice, we investigated the role of miR-21 in IBD and infection. First, we have shown that miR-21 is pathological in chemically induced models of IBD, with miR-21-/- mice protected from the disease relative to wild-type controls. This protection appeared to be in part mediated by the intestinal microbiota of the miR-21-/- mice, as determined by co-housing and germ-free recolonization experiments. 16S sequencing confirmed differences between wildtype and miR-21-/- microbiotas and antibiotic depletion experiments demonstrated that the microbiota is essential for the miR-21-/- protective phenotype. We postulate that miR-21’s negative regulation of the tight junction integrity protein RhoB and the mucin secreting protein MARCKS alter the microbiota through modulation of the intestinal microenvironment. We also sought to characterise miR-21’s role in infection, and demonstrated that miR-21 limits macrophages invasion the grampositive pathogen Listeria monocytogenes, again possibly through modulation of RhoB and MARCKS and their role in phagocytosis. These results have uncovered novel roles for miR-21 in modulation of the host response to commensal and infectious bacteria.
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin